Geopolitical Population Dependency of the Libyan State: A Study in Geopolitics (Journal of Libya for geographical studies, 2026)
This study focuses on highlighting the geopolitical population dependency of Libya. Understanding geopolitical dependency is considered a key factor in determining a state's strength in international relations. Although focusing solely on population size as an indicator of state power and behavior is not considered decisive or objective in geopolitical studies, population-related variables—such as gender ratio, levels of awareness and education, and technological literacy—are essential determinants of the population’s contribution to state power. The geopolitical dependency of Libya’s population relative to neighboring countries is a crucial and effective aspect in assessing state strength and its components. This study relied on 2023 population data from the United Nations. Geopolitical dependency was expressed mathematically using the ratio of the total population of Libya’s neighboring states to Libya’s population. The study analyzed Libya’s geopolitical dependency in relation to its population size and compared it with that of its neighboring countries to identify disparities in dependency rates and examine their effects on Libya’s power, effectiveness, and behavior at regional and international levels.
Keywords: Geopolitical dependency; Libyan population; Neighboring countries